2008
DOI: 10.1186/1471-227x-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stressors and its organizational and individual correlates: A nationwide study of Norwegian ambulance personnel

Abstract: Background: High levels of stress among ambulance personnel have been attributed to the conditions of ambulance work. However, there is little research to support this notion, and it has been questioned whether ambulance work is inherently stressful. We compared the severity and frequency level of organizational and ambulance-specific stressors, and studied their relationship to organizational conditions and individual differences

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 38 publications
6
66
2
6
Order By: Relevance
“…Personal resources such as a sense of coherence have been found to be linked to burnout [18,19]. We found that sense of coherence negatively related with the severity of burnout.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Personal resources such as a sense of coherence have been found to be linked to burnout [18,19]. We found that sense of coherence negatively related with the severity of burnout.…”
Section: Discussionsupporting
confidence: 50%
“…The specific stressors and organizational working conditions in the EMS are more correlated with the frequency of occupational stressors related to the individual characteristics, while general relations between stress at work and individual characteristics are very weak [18]. However, individual characteristics of our respondents were expressed through the experience of stress and response to stress, coping strategies, self-rated health and vitality, a sense of community, sense of coherence and social support which showed a favorable value.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Among EMP, dispatchers had significantly higher scores than other groups for neuroticism, while ambulance drivers scored the lowest in this category (13). Furthermore, neuroticism was strongly related to the severity of stressors and to organizational conditions (14).…”
Section: Big Five Personality and Associated Traitsmentioning
confidence: 96%